MaxHopCount: A New Drop Policy to Optimize Messages Delivery Rate in Delay Tolerant Networks - Harrati, Youssef; Abdali, Abdelmounaim (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
Communication has become a necessity, not only between every point on the earth, but also on the globe. That includes hard topography, highlands, underwater areas, and also space- crafts on other planets. However, the classic wired internet cannot be implemented in such areas, hence, researchers have invented wireless networks. The big challenge for wireless networking nowadays, is maintaining nodes connected in some difficult conditions, such as intermittent connectivity, power failure, and lot of obstacles for the interplanetary networks. In these challenging circumstances, a new networking model arises; it is Delay Tolerant networking which is based on the Store-Carry-and-Forward mechanism. Thus, a node may keep a message in its buffer for long periods of time; until a delivery or forward chance arises then it transmit it to other nodes. One of the big issues that confront this mechanism is the congestion of nodes buffer due to the big number of messages and the limited buffer size. Here, researchers have proposed buffer management algorithms in order to deal with the buffer overload problem, and they called it Drop Policies. In our present work, we propose a new Drop policy which we have compared to other existing policies in different conditions and with different routing protocols, and it always shows good result in term of number of delivered messages, network overhead and also average of latency.
Keywords: network; mobile services; managemet systems; mobility; scheduling; IJIMAI